Understanding the psychological well-being of covid-19 survivors - Legasree, Ravi Chandran (2023)
Psychological well-being of COVID-19 is an important factor that need to be acknowledged. The research is aimed to understand the psychological well-being of COVID 19 survivors. The research question determines psychological well-being of the COVID-19 survivors. A qualitative approach, a semi-structured interview was used to explore the psychological well-being of COVID-19 survivors. The researcher interviewed six COVID-19 survivors in the age range of 21 to 25 years old for the study. The interview was conducted physically with each of the participant. The semi-structured interview protocol explore on the psychological well-being of COVID-19 survivors during and after COVID-19, emotions during quarantine, impact of COVID-19 on the survivors, challenges faced by COVID-19 survivors and the support system of the COVID-19 survivors. The findings shows that the psychological well-being of COVID-19 survivors was affected negatively. However, the current findings do not represent all ethnic, different lifestyle and the needs of COVID-19 survivors. The mental health professionals and future COVID-19 patients can use the current research finding to gain better understanding of the psychological well-being during and after COVID-19.